Correlation of Microscopic and Automated Cell Counter Results of Newer Hematological Variables in Diagnosis and Recovery of Anemia - Ankur, Ahuja; Pankaj, Pandey; PS, Gahlot Gaurav; Sonia, Badwal; Saurabh, Moond; Lal, Dhanetwal Murari (Annals of Pathology and Laboratory Medicine, 2020)
Background: The correct interpretation of new hematological parameters generated by Automated Cell Counters (ACCs) requires extensive knowledge for the clinical significance of these results. The present study will enlighten the vital role of the traditional & new parameters of the Complete Blood Count (CBC) in early diagnosis and follow up stage after treatment especially in the setting of anemia Aims: To evaluate the vast & extended utility of newer hematological parameters generated by ACCs beyond their conventional role of CBC and Differential Leukocyte Count (DLC) Study design: This is a cross sectional observational study of results obtained from blood samples of 100 patients having various types of anemia diagnosed over a period of 18 months Subjects & methods: EDTA blood samples of the patient were collected under aseptic precautions and processed within 2 hours through new generation hematology analyzer i.e. ADVIAR 2120i. The peripheral blood film examination in each case was performed on Leishman-Geimsa stained smear. Second EDTA samples were taken on 2nd and 10th day of follow up of IDA and thalassemia cases respectively. Statistical Analysis Used: The hematological, parameters obtained from ACCs/microscopic were assessed by Student’s t-test, Fisher’s exact test using the SPSS 21.0 software with considering p value < 0.05 as significant Results: IRF and reticulocyte% can distinguish well between IDA and thalassemia major. CHr and MCVr are useful parameter for diagnosis of IDA/thalassemia and vitamin B12 deficiency anemia. CHr is the first parameter for monitoring response treatment of anemia.